2011
DOI: 10.1159/000328969
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life among Elderly Patients with Dementia in Institutions

Abstract: Aim: To study quality of life among the elderly with dementia in institutions. Methods: Patients above 60 years with dementia, 82 in nursing home and 74 in departments of geriatric psychiatry, were included. They were assessed with the Quality of Life in Late-Stage Dementia (QUALID); the Self-Maintenance scale, Mini Mental State Examination (MMSE) and Clinical Dementia Rating scale. Patient’s age, gender, previous medical and psychiatric history were recorded. Dementia was diagnosed according to ICD-10 criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
97
6
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(123 citation statements)
references
References 80 publications
16
97
6
4
Order By: Relevance
“…Although there are nine studies did not find any relationship between demographic characteristics and QoL (Andersen et al, 2004;Grske et al, 2014;Moyle et al, 2015;Monteiro et al, 2014;Sloane et al, 2005;Winzelberg et al, 2005;Wetzels et al, 2010;Salvador et al, 2000), other studies found that higher education (Marventano et al, 2015;Li et al, 2012), males (Woods et al, 2014;Barca et al 2011), white (Black et al, 2012), widowed (Samus et al, 2005) and extroverted characteristic (Li et al, 2012) tended to be positively associated with better QoL for elderly people with dementia. Moreover, Banerjee et al (2005) found that QoL of people with dementia showed decline as with the increasing age, while Mjørud et al (2014) indicated that the QoL was worse among the youngest (<79) and oldest (>90) people with dementia.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are nine studies did not find any relationship between demographic characteristics and QoL (Andersen et al, 2004;Grske et al, 2014;Moyle et al, 2015;Monteiro et al, 2014;Sloane et al, 2005;Winzelberg et al, 2005;Wetzels et al, 2010;Salvador et al, 2000), other studies found that higher education (Marventano et al, 2015;Li et al, 2012), males (Woods et al, 2014;Barca et al 2011), white (Black et al, 2012), widowed (Samus et al, 2005) and extroverted characteristic (Li et al, 2012) tended to be positively associated with better QoL for elderly people with dementia. Moreover, Banerjee et al (2005) found that QoL of people with dementia showed decline as with the increasing age, while Mjørud et al (2014) indicated that the QoL was worse among the youngest (<79) and oldest (>90) people with dementia.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…15 studies (León-Salas et al, 2015;Garre-Olmo et al, 2012;Hodgson 19 et al, 2014;Salvador et al, 2000;Black et al, 2012;Beerens et al, 2014;Beer et al, 2010;Samus et al, 2005;Sloane et al, 2005;Winzelberg et al, 2005;Beerens et al, 2013;Missotten et al, 2007;Barca et al, 2011;Wetzels et al, 2010;Mjørud et al, 2014) concluded that cognitive impairment are inversely associated with QoL of elderly people with dementia, except for Monteiro et al (2014) and . These two studies failed to find a statistically significant association between cognitive status and QoL.…”
Section: Physical Factorsmentioning
confidence: 99%
“…QoL is a multidimensional concept, which in older adults includes behavioural competence, the objective environment, psychological well-being, and perceived QoL (33). QoL among elderly persons with dementia is often diminished (34) due to several factors such as low cognitive function, major depression, lack of social activities, impaired mobility, and low performance in activities of daily living (26,(35)(36)(37). It is documented that older people consider good functioning to be of higher importance than the prevention of diseases (38), and PWDs with higher physical capabilities, such as strength and balance, have scored higher on QoL (26).…”
Section: Introductionmentioning
confidence: 99%
“…Although the optimal place of residence of elderly people is home surroundings, it often happens that even the closest family cannot manage to provide them appropriate care and therefore place their relatives in long-term care centers. Research shows that the level of the quality of life of elderly people is lower among people staying in nursing homes than among those residing in home surroundings [4]. It is estimated that in the USA every fourth person dies in a nursing home, and in Norway this refers even to the half of the society [5].…”
Section: Introductionmentioning
confidence: 99%